DEVELOPMENT OF INTERACTIVE LEARNING MEDIA ON HUMAN RESPIRATORY SYSTEM LEARNING MATERIAL AT GRADE V ELEMENTARY SCHOOL - Siska Dayanti; Mahmud Alpusari; Gustimal Witri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the development of a valid and practical product of interactive learning media on the human respiratory system learning material at grade V elementary school. The method used is Research and Development by using the ADDIE model. This ADDIE model has five stages, Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SD Muhammadiyah Sungai Apit. The research subjects involved 9 fifth-grade students and 3 teachers. The data collection techniques used in the research were interviews, observations, and questionnaires. Data analysis techniques carried out by researchers were descriptive qualitative and quantitative analysis. Qualitative descriptive analysis is used to organize suggestions from validators while quantitative analysis is used to organize validation and practicality questionnaires. The validity test results indicate that the developed interactive learning media achieved a highly valid category with a percentage score of 93.96%. Whereas the practicality of interactive learning media based on the teachers’ response questionnaire was 89.12% with very practical criteria. In addition, based on the student’s response practicality questionnaire was 91.11% with very practical criteria. Hence, it can be concluded that the interactive learning media on the human respiratory system learning material at grade V elementary school has met the valid and practical criteria so that it can be used by teachers and students in the teaching and learning process.